The influence of beams design and the slabs effect on the progressive collapse resisting mechanisms development for RC framed structures. (September 2018) - Bredean, L.A.; Botez, M.D.
Abstract: Using numerical approaches, this paper investigates the structural response of RC framed buildings subjected to accidental/abnormal loads (explosion, impact, etc.). Beside the contribution of the beams, currently considered in the progressive collapse analyses, the effect of the slab structural element through its specific resisting mechanisms (Flexural Action, Yield Line Mechanism, Membrane Action) is also assessed. In addition, the influence of three distinct beam design parameters (the ductility class of the beam longitudinal reinforcement, the beam flexibility in terms of beam height over the beam clear span ratios, respectively the beam longitudinal reinforcement ratio) on the progressive collapse behavior of RC structures is evaluated. Based on previously calibrated numerical models, a consistent series of nonlinear push-down advanced analyses are performed using the Finite Element Method approach. The results indicate that the slab influence is significant at the internal forces transfer and load redistribution mechanisms level: it completely changes the resisting elements behavior when considered in the numerical model. Original findings based on the conducted parametric studies are drawn and compared with results currently available in technical literature. Highlights: A new parameter vσ with impact on the PC resisting mechanisms activation is defined. The CAA resistance resources are not highly sensitive relative to beam flexibility. The CAA load-carrying capacity is limited to 10–25% of the flexural capacity. The slab reinforcement detailing significantly affects the load-carrying capacity.